Windborne debris in the urban environment - Owen, John S. (Wydawnictwo PK, 2015)
This paper presents a comprehensive review of the research into using Windborne debris. It Introduces the components of the typical debris risk model - wind field model, debris generation model, debris trajectory model and debris impact model - and reviews the research That has been done in each of These constituent areas. The majority of this research has focussed on understanding the fundamental physics of debris flight, using both experimental and computational approaches to derive analytical and empirical models. This fundamental physics must be viewed, however, within a probabilistic framework That allows the risk to be Assessed in a relevant | manner. Much of the research Relates to hurricane hazard in the US, however Clearly Windborne debris is a threat to the urban environment duringEuropean wind storms. The Way That FEMA's HAZUS ®MH hazard assessment tool has brought natural hazard modeling into the engineering context is viewed as an approach that could accommodate be adapted for both mitigation and design in a European context.